Pelatihan Tata Kelola Pengembangan Literasi Digital Manajemen Sekolah - Adriantoni, Adriantoni; Gusril Kenedi; Nursyamsi; Nova Wati (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2025)
The problems faced by schools based on direct observation in public and private elementary schools (SDN) are related to the still low governance of digital-based school quality management development. The first problem is that, the principal still has difficulty in preparing a digital-based School Development Plan. Second, the school's work program has not been socialized to the school community. Third, the principal and school development team are still weak in updating information through a digital system. Referring to these problems, the author conducted training and mentoring for the principal and teachers at SDN 16 Padang Pariaman. The method used was Mentoring and Training on digital literacy development. The training participants numbered 10 people, consisting of 1 principal and 9 teachers. The training activities were carried out in the classroom. The results of this service were that the principal and teachers received training on the governance of digital literacy management development of school management. Furthermore, the school must cooperate with the Regency Education Office to improve supporting facilities through an internet network so that school management, especially administration-related, can be carried out digitally to be more effective and efficient. Permasalahan yang dihadapi oleh sekolah berdasarkan pengamatan langsung di sekolah dasar negeri (SDN) dan Swasta yakni berkaitan dengan masih rendahnya tata kelola pengembangan manajemen mutu sekolah berbasis digital. Masalah yang pertama, kepala sekolah masih memiliki kesulitan dalam menyusun Rencana Pengembangan Sekolah berbasis digital. Kedua, program kerja sekolah belum disosialisasikan kepada warga sekolah. Ketiga, kepala sekolah dan tim pengembang sekolah masih lemah dalam mengupdate informasi melalui system digital. Mengacu pada permasalahan tersebut, Penulis melakukan pelatihan dan pendampingan terhadap kepala sekolah dan guru di SDN 16 Padang Pariaman. Metode yang digunakan berupa Pendampingan dan Pelatihan mengenai pengembangan literasi digital. Peserta pelatihan berjumlah 10 orang terdiri dari 1 kepala sekolah dan 9 orang guru. Kagiatan pelatihan dilaksanakan di ruang kelas. Hasil dari pengabdian ini dimana Kepala sekolah dan guru memperoleh pelatihan tentang tata kelola pengembangan manajemen literasi digital manajemen sekolah. Selanjutnya pihak sekolah harus bekerjasama dengan dinas pendidikan Kabupaten untuk meningkatkan sarana penunjang berupa jaringan internet supaya dalam manajemen sekolah terutapa berkaiatan dengan administrasi bisa dilaksankan secara digital supaya lebih efektif dan efisien.